ANALISIS STORE ATMOSPHERE, KUALITAS PELAYANAN DAN KEPUASAN TERHADAP LOYALITAS KONSUMEN PADA TOKO FASHION SASBAG KOTA PARE (STUDI KASUS DI TOKO FASHION SASBAG KOTA PARE) - Khasanah, Uswatul (Universitas Nusantara PGRI Kediri, 2022)
Consumers interested in goods sold by a store are important in a business, so efforts must be made to attract consumer loyalty to the store, by improving the store atmosphere, improving quality and increasing customer satisfaction. The purpose of this study was to determine the analysis of store atmosphere, service quality and satisfaction with consumer loyalty at SASBAG Fashion Stores. This research approach used quantitative research with causal associative techniques. The population and sample of this study were all consumers of the SASBAG fashion store. sampling technique using incidental sampling. The instrument uses a questionnaire whose scores are tested for validity and reliability. The analysis technique uses classical assumption test, multiple linear regression and hypothesis testing.The result, partially and simultaneously variable store atmosphere, service quality and satisfaction have a significant effect on consumer loyalty SASBAG fashion store. it has been proven that the store atmosphere, service quality and satisfaction variables have an effect of 61% on consumer loyalty